ՀՀ դրամ/ԱՄՆ դոլար փոխարժեքի զարգացման միտումների ուսումնասիրությունը ՀՀ-ում 1995-2015թթ - Լիլիթ Գևորգի Պողոսյան (ՀՀ ԳԱԱ հրատ.)
В статье проанализированы динамика и тенденции изменения валютных курсов AMD/USD в РА за послед-ние 21 год. В качестве основы для анализа выбрана трехступенчатая полиномиальная модель. На основе рассчитанных параметров прогнозированы ожидаемые уровни валют для всех кварталов 2016 года. По результатам анализа получено, что к концу 2016 года курс AMD/USD достигнет 624 драмов.The article analyzes the trends in of the Armenian dram to US dollar exchange rate for the period of 21 years (from 1995 to 2015). To analyze the quarterly data, the author relied on a polynomial model, and based on estimation results the authorforecasts exchange rates for each quarter of 2016, and based on the estimates the forecasted value of US dollar to Armenian dram exchange rate could reach 624 Armenian drams in the last quarter of 2016.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ